Geopolitical features of the position of Serbia and Serbian nation in modern international relations - Glišin, Vanja (Napredak, 2025)
In this paper, the author analyzes geopolitical features of the position of Serbia and Serbian nation in the context of current international circumstances, with a focus on the Russian-Ukrainian conflict. Geopolitical features which will be the subject of the analysis are: knottiness, borderliness and fragmentation, since these are the paradigmatic features of the Balkan territory. Having this in mind, in this paper we will define the above-listed features so as to be able to analyze them further in the given contexts. We will analyze in particular how the former and the latter affect the conflict and, accordingly, make a synthesis and show how their consequences are reflected on the position of Serbia and Serbian nation. In addition to the description, analysis and synthesis methods, we will also use the geopolitical method for the purpose of understanding a strong cause-and-effect relationship between the political and the spatial in the current context. It is assumed that the ongoing conflicts complicate the geopolitical features of the position of Serbia and Serbian nation and aggravate the international position between the East and the West.